Construction creativity casebook - Langford, D. A. (Thomas Telford, 2002)
Many innovations in the UK construction industry are developed in response to the government initiatives based on the Egan Report. This publication provides a background and profile of innovations in the UK construction industry though an analysis of the innovations presented within the NCCC.